(untitled) (Ameghiniana, 2016)
Although sexual size dimorphism is an important component of the biology of many living New World metatherians, little is known about sexual dimorphism in extinct members of this group. Here, we describe morphometric variation in two traditionally recognized species of the paucituberculatan Acdestis from the early Miocene Santa Cruz Formation of Patagonia, A. owenii and A. spegazzinii (=A. lemairei). The results of this morphometric study show that specimens of Acdestis from the Santa Cruz Formation form a single morphological continuum, with no features that clearly distinguish the two recognized morphotypes besides overall body size and the depth of the mandibular ramus, both features which are sexually variable in extant marsupials. This suggests that the two species of Acdestis from the Santa Cruz Formation are better regarded as gender morphs of a single dimorphic species rather than two highly similar monomorphic species. The degree of sexual dimorphism inferred here for Acdestis is comparable to that seen in living sexually dimorphic marsupials. The identification of sexual dimorphism in Acdestis suggests that extinct paucituberculatans may have exhibited much greater variation in their ecology and life history than currently predicted based on extant members of this group. Resumen. EVIDENCIAS DE DIMORFISMO SEXUAL EN EL PALAEOTHENTIDAE DEL MIOCENO TEMPRANO ACDESTIS OWENII (MARSUPIALIA: PAUCITUBERCULATA). Aunque el dimorfismo sexual es un componente importante de la biología de muchos metaterios actuales del Nuevo Mundo, se sabe poco sobre el dimorfismo sexual en miembros extintos de este grupo. Aquí, describimos la variación morfométrica en dos especies tradicionalmente reconocidas del paucituberculado Acdestis de la Formación Santa Cruz (Mioceno de Patagonia), A. owenii y A. spegazzinii (=A. lemairei). Los resultados de este estudio morfométrico indican que los ejemplares de Acdestis de la Formación Santa Cruz constituyen un único continuo morfológico, no habiendo rasgos que permitan distinguir claramente los dos morfotipos reconocidos aparte del tamaño general y la profundidad de la rama mandibular –rasgos que pueden variar con el sexo en los marsupiales vivientes. Esto sugiere que es preferible considerar las dos especies de Acdestis de la Formación Santa Cruz como morfos de una sola especie dimórfica antes que dos especies monomórficas muy parecidas. El grado de dimorfismo sexual en Acdestis que se infiere aquí es comparable al visto en marsupiales vivientes sexualmente dimórficos. La identificación de dimorfismo sexual en Acdestis sugiere que los paucituberculados extintos podrían haber mostrado mucha más variabilidad en su ecología y ciclo biológico que lo que se predice actualmente basado en los miembros vivientes del grupo.